Adsorption behavior of hydrophobin and hydrophobin/surfactant mixtures at the solid-solution interface. - Zhang, X; Penfold, J; Thomas, R; Tucker, I; Petkov, J; Bent, J; Cox, A (2011)
The adsorption of surface-active protein hydrophobin, HFBII, and HFBII/surfactant mixtures at the solid-solution interface has been studied by neutron reflectivity, NR. At the hydrophilic silicon surface, HFBII adsorbs reversibly in the form of a bilayer at the interface. HFBII adsorption dominates the coadsorption of HFBII with cationic and anionic surfactants hexadecyltrimethyl ammonium bromide, CTAB, and sodium dodecyl sulfate, SDS, at concentrations below the critical micellar concentration, cmc, of conventional cosurfactants. For surfactant concentrations above the cmc, HFBII/surfactant solution complex formation dominates and there is little HFBII adsorption. Above the cmc, CTAB replaces HFBII at the interface, but for SDS, there is no affinity for the anionic silicon surface hence there is no resultant adsorption. HFBII adsorbs onto a hydrophobic surface (established by an octadecyl trimethyl silane, OTS, layer on silicon) irreversibly as a monolayer, similar to what is observed at the air-water interface but with a different orientation at the interface. Below the cmc, SDS and CTAB have little impact upon the adsorbed layer of HFBII. For concentrations above the cmc, conventional surfactants (CTAB and SDS) displace most of the HFBII at the interface. For nonionic surfactant C(12)E(6), the pattern of adsorption is slightly different, and although some coadsorption at the interface takes place, C(12)E(6) has little impact on the HFBII adsorption.